MODELING CHARACTER EDUCATION IN ISLAMIC BOARDING SCHOOL THROUGH ECOLOGICAL SYSTEM THEORY: A CASE STUDY AT GONTOR 10 JAMBI - Sucianingtyas, Richa; Arifin, Syamsul; Rudianto; Masruhin, Salis (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2025)
This study examines character education at Pondok Modern Darussalam Gontor, Campus 10 Jambi, using Bronfenbrenner’s Ecological System Theory (EST). Unlike most studies focusing on formal schools, it highlights the underexplored pesantren context. A qualitative case study was conducted through observations, interviews, and document analysis with leaders, teachers, and students. Findings show that character formation occurs holistically: the microsystem (dormitories, classrooms, mosques) fosters discipline; the mesosystem (teacher–mentor relations) ensures consistency; the exosystem (central policies) provides uniformity; the macrosystem (Panca Jiwa) grounds values; and the chronosystem reflects curricular adaptation. The novelty lies in the development of a Religious Ecological System Theory that integrates spiritual dimensions into EST. Practically, this model serves as a reference for designing adaptive and sustainable strategies in character education. Penelitian ini menganalisis implementasi pendidikan karakter di Pondok Modern Darussalam Gontor Kampus 10 Jambi melalui Ecological System Theory (EST) Bronfenbrenner. Berbeda dari kajian terdahulu yang berfokus pada sekolah formal, penelitian ini menyoroti konteks pesantren yang masih jarang diteliti. Menggunakan metode kualitatif studi kasus, data dikumpulkan melalui observasi, wawancara, dan analisis dokumen dengan pimpinan, guru, dan santri. Hasil menunjukkan pembentukan karakter berlangsung holistik: mikrosistem (asrama, kelas, masjid) menanamkan kedisiplinan; mesosistem (relasi guru–pembina) menjaga konsistensi; eksosistem (kebijakan pusat) memberi standar seragam; makrosistem (Panca Jiwa) menjadi fondasi nilai; dan kronosistem mencerminkan adaptasi kurikulum. Kebaruan penelitian ini adalah pengembangan Religious Ecological System Theory yang menekankan dimensi spiritual. Model ini memberi rujukan praktis bagi lembaga pendidikan lain untuk strategi penguatan karakter yang adaptif dan berkelanjutan.